Programa de Melhoria do Acesso e da Qualidade da Atenção Básica: Uma análise e comparação dos dados do terceiro ciclo. - Silva, Catiucia Aparecida da (2022)
Primary Health Care interposes each individual with their sociocultural uniqueness, in the search for equity and comprehensive care through decentralization and capillarity, promoting access to the system and facilitating a connection throughout the Health Care Network. Through the tool or evaluation mechanism in the health service, it is a guide to consolidate in its various lines of approaches, which have been gaining their own contours, materializing specific forms and concepts, indicators and appropriate application techniques. Therefore, evaluation in the health service is an area already consolidated in its various lines of approaches such as: access, work process, structures, materials, functioning, among others. Thus, the present research aims to analyze and compare the data of the third cycle of the Program for the Improvement of Access and Quality of Primary Care, being divided into two stages, the first was the survey of the National Identifier of the homologated Teams in the total of 521, with the classification excellent, very good, good, regular, bad, unsatisfactory and unclassified of the 79 municipalities in the state of Mato Grosso do Sul and in the second stage descriptive process of the resourcefulness of the four macro-regions of the state of MS, specifically the data from Dimension III (Valuation of the worker), for having the second highest weight per question (0.3333 weights eSF with oral health and 0.2500 weight without oral health), opening questions and possibilities through active and deactivated programs of primary health care, triggering and punctuating the relevance of each one, through the mechanisms of protection to professionals in the areas of education and health and in digital health, the guidelines and clearly reflecting on the resourcefulness of the system in relation to health work. As far as it is concerned, it presents a descriptive quantitative research, secondary data belonging to the database of the Department of Primary Care (DAB), component of its external evaluation. The results showed that the strengthening of knowledge that matrix and institutional support provides to workers in a unique way, enhancing work in the health network. It is concluded that the classifications of the state of Mato Grosso do Sul performed well with the program, certifying that the state was working to provide primary health care with access, improvement and quality within the RAS. The change in the evaluation culture as a qualification and strategy tool during the cycles applied with the valorization and protection of workers over work contributed to the development of the offer of health promotion and prevention actions, pointing out that the evaluation is an instrument guide and driver for effectiveness health teams in order to reach the final goal, which is to reach and maintain the indicators with the purpose of reaching the pinnacle of financial incentives according to the final classification of each team.